La herencia de las Sententiae de Publilio Siro en las paremias españolas en torno a la avaricia - Pascual-López, Xavier (Studia Romanica Posnaniensia, 2019)
The aim of this paper is to present the Spanish proverbs related to the topic of greed that can be understood as a continuation of Publilius Syrus’ sentences. For the analysis are taken into account the contributions of two Hellenistic philosophical schools (Stoicism and Epicureanism), which illuminate the scope of the criticism of greed that occurs in these proverbs, both from a psychological as a social point of view. Latin sentences and Spanish proverbs are compared according to their formal or semantic continuity, as well as depending on other aspects (such as the tone or prosodic issues).